Exploring Developmental Biology: The Influence of Sexual Education and Social Awareness on Elementary School Children - Abela Mayunita; Nurmida Bintang; Puspa Dila; Anjarsari Putri; Rani Rachmawati; Wardah; Widia Nurkamileti (Postgraduate, University of Mataram, 2024)
This research explores how sexual education and social awareness influence children's knowledge about sexual violence, bullying, and cybercrime. Education in these early stages of developmental biology is critical because children are forming their cognitive and social capacities. This research used a simple random sampling technique to select samples based on the Slovin formula and collected primary data through a pretest-posttest questionnaire. Analysis using a paired sample t-test shows a significant increase in children's understanding of these topics after education. Conclusions from the study suggest the continuation and support of sexual education and social awareness programs, given their effectiveness in increasing awareness and knowledge at an early age. It is recommended that educational institutions and parents support the implementation of similar programs that can facilitate healthy and proactive social development among elementary school children, with further research needed to optimize these educational components in various social contexts